2012
DOI: 10.1039/c2cc31712e
|View full text |Cite
|
Sign up to set email alerts
|

High performance silicon nanoparticle anode in fluoroethylene carbonate-based electrolyte for Li-ion batteries

Abstract: Electrodes composed of silicon nanoparticles (SiNP) were prepared by slurry casting and then electrochemically tested in a fluoroethylene carbonate (FEC)-based electrolyte. The capacity retention after cycling was significantly improved compared to electrodes cycled in a traditional ethylene carbonate (EC)-based electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
225
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(235 citation statements)
references
References 16 publications
9
225
1
Order By: Relevance
“…7). We believe that this is the explanation for frequently reported long cycle life of cells with silicon anodes and FEC co-solvent if tested in coin cells (>hundreds of cycles), 25,46 while to our knowledge this has never been reported for actual batteries, in which the amount of electrolyte in terms of μL/cm 2 is much smaller.…”
Section: Cellmentioning
confidence: 88%
See 3 more Smart Citations
“…7). We believe that this is the explanation for frequently reported long cycle life of cells with silicon anodes and FEC co-solvent if tested in coin cells (>hundreds of cycles), 25,46 while to our knowledge this has never been reported for actual batteries, in which the amount of electrolyte in terms of μL/cm 2 is much smaller.…”
Section: Cellmentioning
confidence: 88%
“…This is consistent with the literature, which shows that the use of FEC as co-solvent (typically ≥10% wt FEC) strongly stabilizes the cycle-life of silicon anodes. 22,25,46 The cycle number of the Si-Li cells at which the rapid capacity drop occurs is depicted by the black symbols in Fig. 7 (data from Figs.…”
Section: Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Si is well known to suffer from severe volume change during reaction with lithium 3 followed by electrochemical and mechanical particle disintegration 2,4 leading to a poor cycling ability. Recent reports have shown that the use of amorphous 5 or nanostructured Si, 6 and carboncoating 7,8 or carbon composite, [9][10][11] and the use of advanced elastic binder [12][13][14] and electrolyte composition 15,16 yields enhancement of cycling ability. It still however remains a great challenge to develop new approaches for obtaining a reliable performance of lithium-ion batteries employing Si-based anodes.…”
mentioning
confidence: 99%